26 | Health Action Zones profiling and protected discharge pathways in mental health: proposal of an integrated hospital–community care model in ASP Palermo - E. Modica; A. Di Benedetto; A. Li Puma; D. Lipari; A. Firenze (Journal of Biological Research - Bollettino della Società Italiana di Biologia Sperimentale, 2026)
Background. Continuity of care is one of the most critical challenges in the management of patients with severe mental disorders who are at high risk of relapse and rehospitalization. Hospital discharge represents a crucial transition phase during which inadequate integration between hospital and community services may lead to treatment discontinuity and poor clinical outcomes. Analysis of psychiatric hospitalization data within ASP Palermo highlighted a high prevalence of admissions related to psychotic disorders, often characterized by recurrent hospitalizations and difficulties in maintaining adherence to community-based care pathways. Materials and Methods. A retrospective observational analysis was conducted on psychiatric inpatient admissions recorded during 2025 in the main hospitals of ASP Palermo. A total of 2,185 hospitalizations were examined. Hospital discharge data were integrated with the Sicilian Health Action Zones (HAZ) dashboard to develop a risk-stratification model aimed at supporting protected discharge planning. Patients were categorized into low-, medium-, and high-risk groups according to both clinical and territorial vulnerability indicators. Different levels of post-discharge intervention were then associated with each risk category. Results. The proposed model enables the allocation of tailored community care pathways according to the identified risk profile. Low-risk patients are referred to standard outpatient follow-up, while medium-risk subjects are rapidly linked to Community Mental Health Centers (CMHCs). High-risk patients receive intensive multidisciplinary monitoring and, when necessary, home-based interventions. The integration of HAZ indicators allows early identification of individuals living in socioeconomically vulnerable areas, who are more likely to experience poor treatment adherence, repeated emergency department visits, and hospital readmissions. The model therefore supports a more targeted allocation of healthcare resources and strengthens coordination between hospital and community services. Conclusions. The application of HAZ profiling to mental health discharge planning represents an innovative governance tool that combines clinical and territorial determinants of risk. This integrated approach may improve continuity of care, enhance the appropriateness of post-discharge interventions, and contribute to reducing preventable rehospitalizations. Furthermore, it provides healthcare organizations with a population health management framework capable of supporting strategic planning and resource allocation in mental health services.